Prior Use of 3-Hydroxy-3-Methyl-Glutaryl-Coenzyme A Reductase Inhibitor, Simvastatin Fails to Improve Outcome after Experimental Intracerebral Hemorrhage - Jwa, Cheol-Su (The Korean Neurosurgical Society, 2011)
OBJECTIVE: Contrary to some clinical belief, there were quite a few studies regarding animal models of intracerebral hemorrhage (ICH) in vivo suggesting that prior use of statins may improve outcome after ICH. This study reports the effect of 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG CoA) reductase inhibitor, simvastatin given before experimental ICH. METHODS: Fifty-one rats were subjected to collagenase-induced ICH, subdivided in 3 groups according to simvastatin treatment modality, and behavioral tests were done. Hematoma volume, brain water content and hemispheric atrophy were analyzed. Immunohistochemical staining for microglia (OX-42) and endothelial nitric oxide synthase (eNOS) was performed and caspase-3 activity was also measured. RESULTS: Pre-simvastatin therapy decreased inflammatory reaction and perihematomal cell death, but resulted in no significant reduction of brain edema and no eNOS expression in the perihematomal region. Finally, prior use of simvastatin showed less significant improvement of neurological outcome after experimental ICH when compared to post-simvastatin therapy. CONCLUSION: The present study suggests that statins therapy after ICH improves neurological outcome, but prior use of statins before ICH might provide only histological improvement, providing no significant impact on neurological outcome against ICH.